Assessing the potential cost of a failed Doha Round - Bouët, Antoine; Laborde Debucquet, David (Cambridge University Press, 2010)
This study offers new conclusions on the economic cost of a failed Doha Development Agenda (DDA). We assess potential outcome of the Doha Round as well as four protectionist scenarios using the MIRAGE Computable General Equilibrium (CGE) model. In a scenario where applied tariffs of World Trade Organization (WTO) economies would go up to currently bound tariff rates, world trade would decrease by 9.9% and world welfare by US$353 billion. The economic cost of a failed DDA is here evaluated by the difference between a cooperative scenario (DDA) and a protectionist one (US$412 billion in terms of welfare). Another point of view is to compare a resort to protectionism when the DDA is implemented with a resort to protectionism when the DDA is not implemented. The findings show that this trade agreement could prevent the potential reduction of US$809 billion of trade and, therefore, acts as an efficient multilateral ‘preventive’ scheme against the adverse consequences of trade ‘beggar-thy-neighbor’ policies.